Shrub encroachment alters the diversity of soil fungal communities in topsoil, but not in subsoil under alpine grassland of the Qinghai-Tibetan plateau - Wenming Ma; Tenzing Droma; Changting Wang; Xiangli Ma (Global Ecology and Conservation)
Encroachment of alpine grassland ecosystems by shrubs is widespread in the Qinghai-Tibetan Plateau. However, effects of shrub encroachment on fungal community structure and its function are limited. The objective of this study was to elucidate the response of soil organic carbon composition, soil fungal community, and their functions to shrub encroachment within the same region. We investigated soil fungal communities in top- and subsoils of shrub-encroached patches (Potentilla fruticosa, Spiraea alpina and Caragana microphylla) and the open grassland using nuclear ribosomal DNA internal transcribed spacer (ITS). A total of 48 samples were collected. The Fourier Translation Infrared spectroscopy (FTIR) was conducted to assess the soil organic carbon (SOC) chemical composition. Potential fungal functions were explored using FUNGuild. Both top- and subsoils, total nitrogen (TN) and SOC contents did not alter under shrub patches compared to the open grassland (control sites) (TN, F=1.460, p = 0.24; SOC, F=1.294, p = 0.267). The aromatic groups were dominant fraction in SOC at top- and subsoils under shrub-encroached and unencroached sites. Shrub encroachment exhibited a higher fungal diversity in topsoil, and a significantly different fungal community composition in top- and subsoils compared with open grassland. Results of FUNGuild showed saprotroph was the dominant fungal trophic mode among the P. fruticosa, S. alpina and C. microphylla patches, and saprotroph in P. fruticosa and S. alpina were significantly higher than open grassland in the topsoil (F=6.621, p = 0.028; F=8.224, p = 0.017), not in the subsoil (F=0.467, p = 0.510; F =2.888, p = 0.120). Co-occurrence networks between fungal taxa showed higher network links and more assembled, indicating the stability of fungal community was promoted by shrub development. Hierarchical partitioning (HP) analysis indicated that pH and SOC were the main key factors affecting fungal community structure in top- and subsoils, respectively. Shrub encroachment in alpine grassland leads to soil fungi preferring to utilize the relatively accessible recalcitrant SOC (aliphatic group), and causes enrichment of copiotrophic fungi.